2020
DOI: 10.1186/s12955-020-01604-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life status determinants in hypertrophic cardiomyopathy as evaluated by the Kansas City Cardiomyopathy Questionnaire

Abstract: Purpose The present study evaluated how heart failure (HF) negatively impacts health-related quality of life (HRQoL) in hypertrophic cardiomyopathy (HCM) patients and explored the major clinical determinants associated with HRQoL impairment in this population. Methods This was a cross-sectional single-center study of health-related HRQoL that included 91 consecutive patients with HCM. Evaluation was performed based on a comprehensive protocol that included the recommended diagnostic studies, as well as admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…Past research found that patients with HCM experienced some reduction in health-related quality of life. 22 Additionally, the continuum and variability of psychological impacts after diagnosis were highlighted in our findings, including anxiety, denial, and upset feelings as well as more positive feelings of gratitude, acceptance, and increased mindfulness toward healthy habits. Past research found that patients with heart disease reported feeling different from others, 7 feeling negatively around lost health and control, 8 and experiencing anxiety around cardiac symptoms and their possible catastrophic consequences.…”
Section: Discussionmentioning
confidence: 53%
“…Past research found that patients with HCM experienced some reduction in health-related quality of life. 22 Additionally, the continuum and variability of psychological impacts after diagnosis were highlighted in our findings, including anxiety, denial, and upset feelings as well as more positive feelings of gratitude, acceptance, and increased mindfulness toward healthy habits. Past research found that patients with heart disease reported feeling different from others, 7 feeling negatively around lost health and control, 8 and experiencing anxiety around cardiac symptoms and their possible catastrophic consequences.…”
Section: Discussionmentioning
confidence: 53%
“…Previous series revealed that physical limitation as categorized by NYHA class was an independent risk factor for poor quality of life. 15 Septal reduction therapy by myectomy ameliorates heart failure symptoms and can result in improved quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Previous series revealed that physical limitation as categorized by NYHA class was an independent risk factor for poor quality of life. 15 Septal reduction therapy by myectomy ameliorates heart failure symptoms and can result in improved quality of life. Previously, Wells and colleagues reported improvement in physical capacity from NYHA class III/IV to class I/II in 96% of patients after SM for obstructive HCM.…”
Section: Discussionmentioning
confidence: 99%
“…QoL quality of life, EQ-5D-5L EuroQol questionnaire, KCCQ Kansas City cardiomyopathy questionnaire, iMCQ medical consumption questionnaire, iPCQ productivity cost questionnaire about broader cost types [10][11][12]. Furthermore, QoL studies are rare and none have measured QoL with the EQ-5D-5L, the required instrument according to Dutch guidelines [5,[13][14][15]. The AFFECT-HCM (Quality of Life and Costs in HCM) study aims to estimate the one-year impact of HCM on generic and disease-specific QoL and the societal costs of HCM in the Netherlands.…”
Section: Subject Follow-up Finalisationmentioning
confidence: 99%